Tantangan Perkembangan Kemampuan Matematis Siswa Indonesia dalam Kurikulum Merdeka (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to identify and analyze the challenges in developing Indonesian students’ mathematical abilities within the implementation of the Merdeka Curriculum. Using a literature review method, 14 out of 30 reviewed articles were found relevant. The findings highlight key challenges such as gaps in foundational literacy and numeracy, low teacher quality, limited learning resources, lack of innovation in mathematics instruction, suboptimal formative assessments, and low student motivation. Although the Merdeka Curriculum promotes student-centered learning with flexibility, its implementation still faces significant barriers. Therefore, targeted strategies are needed, including teacher training, provision of adequate resources, and collaboration between educational institutions and the government. This review offers valuable implications for policy development aimed at improving the quality of mathematics education in Indonesia.